Species diversity, mosquito behavior, and microfilariae detection in vectors and reservoirs in filariasis-endemic areas of Bengkulu, Indonesia - DERI KERMELITA; UPIK KESUMAWATI HADI; SUSI SOVIANA; RISA TIURIA; DIMAS NOVIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kermelita D, Hadi UK, Soviana S, Tiuria R, Novianto D. 2024. Species diversity, mosquito behavior, and microfilariae detection in vectors and reservoirs in filariasis-endemic areas of Bengkulu, Indonesia. Biodiversitas 25: 3125-3131. Filariasis, recognized by the WHO as a neglected tropical disease, remains a significant global health challenge, particularly in Southeast Asia. In Bengkulu Province, Indonesia, 66 cases of filariasis were reported between 2010 and 2020, with the highest prevalence found in Mukomuko and Seluma Districts. This study analyzed the vector behavior and detection of filariasis reservoirs in endemic areas of Bengkulu Province. Human landing and resting collections were employed for mosquito collection for 12 h (18:00-06:00), and blood sampling was performed on reservoir animals (Canis familiaris, Felis catus Linnaeus, 1758, and Macaca fascicularis (Raffles, 1821)). Mosquito diversity was analyzed using several diversity indices. Filaria larvae in mosquitoes were detected using Polymerase Chain Reaction (PCR) methods, and filaria in reservoir animals were detected using blood smears with Giemsa staining. The result showed that 17 mosquito species were captured in the filariasis-endemic regions of Bengkulu Province: Culex quinquefasciatus Say, 1823; Culex hutchinsoni Barraud, 1924; Culex gelidus Theobald, 1901; Culex pseudovishnui Colless, 1957; Culex vishnui Theobald, 1901; Armigeres subalbatus (Coquillett, 1898); Aedes aegypti (Linnaeus, 1762); Aedes albopictus (Skuse, 1894); Anopheles tessellatus Theobald, 1901; Anopheles vagus Döntiz, 1902; Anopheles minimus Theobald, 1901; Anopheles indefinitus (Ludlow, 1904); Anopheles sundaicus (Rodenwaldt, 1948); Anopheles barbirostris Wulp, 1884; Anopheles maculatus Theobald, 1901; Anopheles sp., and Mansonia annulata Leicester, 1908. Culex pseudovishnui exhibited the highest indoor density among the mosquito species, whereas C. quinquefasciatus exhibited the highest outdoor density. Filaria larvae were not detected in all mosquito sample pools based on the PCR results, whereas microfilariae of Dirofilaria immitis (Leidy, 1856) Railliet & Henry, 1911 were identified in the reservoir (Canine) blood samples. Thus, the presence of microfilariae in reservoir animals must be monitored because they can transmit filariasis to the community. Control strategies should be developed for endemic regions in Bengkulu Province.